The Relationship of Therapy and The Quality of Life in Senile Cataract Patients in NTB Provincial Hospital for The Period of January – March 2023 - Wahyudi, Belynda Rahmalia Sanceska; Suryani, Dewi; Andari, Marie Yuni (Jurnal Biologi Tropis, 2024)
Cataract is the second highest number causing blindness in Indonesia. The common type of cataract that is often found in NTB Province is Senile Cataract. The definitive treatment for cataracts is surgery, however, several senile cataract sufferers at the NTB Provincial Regional Hospital still choose medical treatment over surgery. This has an impact on the quality of life. This research aims to explore the relationship between medical and operation treatment towards the quality of life of Senile Cataract patient. A systematic random sampling method was carried out on Senile Cataract patients at the Provincial Regional Hospital who had received medical therapy or surgery from January - March 2023. Data collection used a guided interview method by filling in the NEI-VFQ 25 questionnaire which specifically assesses vision. The total sample size for this study was 36 respondents (18 respondents for both surgical and medical treatment). Based on this research, it was found that the majority of subjects who received medical therapy had an adequate quality of life. The majority of subjects who received surgical therapy had a good quality of life. Through this research, it is also known that the best type of therapy to improve the quality of life in Senile Cataract patients is surgical therapy. As a conclusion, the medical therapy and surgery have a relationship with the quality of life of senile cataract patients at the NTB Provincial Regional Hospital, but they have differences in terms of the resulting quality of life.